2020
DOI: 10.1016/j.tmaid.2020.101738
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment of COVID-19 patients with hydroxychloroquine and azithromycin: A retrospective analysis of 1061 cases in Marseille, France

Abstract: Background: In France, the combination hydroxychloroquine (HCQ) and azithromycin (AZ) is used in the treatment of COVID-19. Methods: We retrospectively report on 1061 SARS-CoV-2 positive tested patients treated for at least three days with the following regimen: HCQ (200 mg three times daily for ten days) + AZ (500 mg on day 1 followed by 250 mg daily for the next four days). Outcomes were death, clinical worsening (transfer to ICU, and > 10 day hospitalization) and viral shedding persistence (> 10 days). Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
472
3
40

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(527 citation statements)
references
References 25 publications
12
472
3
40
Order By: Relevance
“…Two recent studies that support targeting the endocytic pathway and autophagy as therapeutic strategies are by Arshad et al and Lagier et al, both of which show that HCQ was associated with a signi cant reduction of in-hospital mortality compared to those not receiving HCQ [31,32]. Numerous other studies have also reported the e cacy of CQ and/or HCQ in various treatment regimens for COVID-19 [33][34][35][36][37][38][39]. Adding to the complexity of COVID-19 treatment and prevention, is that SARS-CoV-2 appears to be mutating at an alarming rate, as reported in the Icelandic study which identi ed the presence of 291 sequence variants that were not present in the Global Initiative on Sharing All In uenza Data (GISAID) reference database as of March 22 (11).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies that support targeting the endocytic pathway and autophagy as therapeutic strategies are by Arshad et al and Lagier et al, both of which show that HCQ was associated with a signi cant reduction of in-hospital mortality compared to those not receiving HCQ [31,32]. Numerous other studies have also reported the e cacy of CQ and/or HCQ in various treatment regimens for COVID-19 [33][34][35][36][37][38][39]. Adding to the complexity of COVID-19 treatment and prevention, is that SARS-CoV-2 appears to be mutating at an alarming rate, as reported in the Icelandic study which identi ed the presence of 291 sequence variants that were not present in the Global Initiative on Sharing All In uenza Data (GISAID) reference database as of March 22 (11).…”
Section: Discussionmentioning
confidence: 99%
“…A follow‐up retrospective study from this French group evaluated 1061 patients, 46.4% male, mean age 43.6 years, with an age range of 14 to 95 years. It reported a favorable clinical outcome with a virologic cure in 973 of the 1061 patients within 10 days when using a combination of HCQ and azithromycin 2 . Other studies involving hospitalized patients have been less encouraging 3 .…”
Section: Introductionmentioning
confidence: 99%
“…18.40, 95% CI 6.28 to 53.90), and medium and high National Early Warning Score (NEWS; OR: 9.48, 95% CI 3.25 to 27.66; OR = 10.05, 95% CI 3.16 to 32.02, respectively) were signi cantly associated with poor clinical outcome. Cardiac toxicity was not reported in the study [19]. Although cardiac toxicity was not reported in any of the studies, a study by Chorin et al reported an extension in QT interval in SARS-CoV-2-positive patients treated with hydroxychloroquine, suggesting a risk of arrhythmia [20].…”
Section: Chloroquine and Hydroxychloroquinementioning
confidence: 79%